2015
DOI: 10.1038/jid.2015.186
|View full text |Cite
|
Sign up to set email alerts
|

Palmoplantar Pustular Psoriasis Is Associated with Missense Variants in CARD14 , but Not with Loss-of-Function Mutations in IL36RN in European Patients

Abstract: Endogenous expression of Hras(G12V) induces developmental defects and neoplasms with copy number imbalances of the oncogene. Proc Natl Acad Sci USA 106: 7979-84 Davies H, Bignell GR, Cox C et al. (2002) Mutations of the BRAF gene in human cancer. Nature 417:949-54 Dhomen N, Da Rocha Dias S, Hayward R et al. (2010) Inducible expression of (V600E) Braf using tyrosinase-driven Cre recombinase results in embryonic lethality. Pigment Cell Melanoma Res 23:112-20 Groesser L, Herschberger E, Ruetten A et al. (2012) Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 16 publications
5
75
3
3
Order By: Relevance
“…Since then, several studies have reported associations of CARD14 variants with psoriasis vulgaris, psoriatic arthritis, generalized pustular psoriasis, and palmoplantar pustular psoriasis (Ammar et al, 2013(Ammar et al, , 2016Eskin-Schwartz et al, 2016;Feng et al, 2016;Gonzalez-Lara et al, 2013;Inoue et al, 2016;Korber et al, 2013;Mossner et al, 2015;Qin et al, 2014;Sugiura et al, 2014Sugiura et al, , 2015Zhu et al, 2016). Furthermore, CARD14 variants have also been associated with pityriasis rubra pilaris, a distinct inflammatory skin disease characterized by keratotic follicular papules and salmon-colored erythematous plaques (Eytan et al, 2014;Fuchs-Telem et al, 2012;Has et al, 2016;Inoue et al, 2016;Li et al, 2015).…”
Section: Card14 Variants In Psoriasismentioning
confidence: 94%
See 1 more Smart Citation
“…Since then, several studies have reported associations of CARD14 variants with psoriasis vulgaris, psoriatic arthritis, generalized pustular psoriasis, and palmoplantar pustular psoriasis (Ammar et al, 2013(Ammar et al, , 2016Eskin-Schwartz et al, 2016;Feng et al, 2016;Gonzalez-Lara et al, 2013;Inoue et al, 2016;Korber et al, 2013;Mossner et al, 2015;Qin et al, 2014;Sugiura et al, 2014Sugiura et al, , 2015Zhu et al, 2016). Furthermore, CARD14 variants have also been associated with pityriasis rubra pilaris, a distinct inflammatory skin disease characterized by keratotic follicular papules and salmon-colored erythematous plaques (Eytan et al, 2014;Fuchs-Telem et al, 2012;Has et al, 2016;Inoue et al, 2016;Li et al, 2015).…”
Section: Card14 Variants In Psoriasismentioning
confidence: 94%
“…Dectin-1, like other immune receptors (e.g., T cell receptor, B cell receptor, and NKG2D), employs immunoreceptor tyrosine-based activation motifs (ITAMs) to initiate downstream signaling via Src kinases (Thome, 2008). In T cells, Src kinase activity eventually leads to the activation of PKCq, which in turn phosphorylates and activates CARD11 (Jordan et al, 2012a;Mossner et al, 2015;Sugiura et al, 2014;Zhu et al, 2016) p.Arg179His 4 CC PsV/PPP 1.38 (Jordan et al, 2012a;Mossner et al, 2015) p.Val191Leu 4 CC PsV 1.02 (Jordan et al, 2012a) p.Glu197Lys 4 CC PPP/PsV/PsA 1.667 (Ammar et al, 2016;Mossner et al, 2015) p.Ser200Asn 4 CC PsV/GPP/PPP 0.67 (Ammar et al, 2016;Jordan et al, 2012a;Korber et al, 2013;Mossner et al, 2015) p.Leu209Pro 4 CC PsV 0.785 (Ammar et al, 2016) p.Ala216Thr 4 CC PsV 0.575 (Ammar et al, 2016;Qin et al, 2014;Zhu et al, 2016) p.Asp285Gly 6 None PsV 1.14 (Jordan et al, 2012a) p.Met338Val 7 CC PsV 0.914 (Ammar et al, 2016) p.Thr420Ala 9 none PsV 0.663 (Ammar et al, 2016) c.1356þ5G>A 9 CC PsV ND (Ammar et al, 2016) p.Thr591Met 13 PDZ PsV ND (Qin et al, 2014) p.Ile593 Asn 13 PDZ PsV 1.30 Jordan et al (2012a) p.Ser602Leu 13 PDZ PsV/GPP/PPP 1.196 (Ammar et al, 2016) p.Arg682Trp 15 SH3 PsV/GPP 0.95 (Jordan et al, 2012a;Qin et al, 2014) p.Gly714Ser 15 SH3 PsV 1.02 (Jordan et al, 2012a) p.Arg820Trp 18 GUK PsV/PsA ND (Feng et al, 2016;Gonzalez-Lara et al, 2013;Jordan et al, 2012a;Sugiura et al, 2015) p.Asp973Glu 21 GUK PsV ND (Jordan et al, 2012a) Details on the location of the mutations, their disease occurrence, and their effect on NF-kB activation is shown. The exon sequence was determined using transcript CARD14-201 (ENST00000344227 …”
Section: Card14-mediated Activation Of Paracaspase Malt1mentioning
confidence: 99%
“…CARD14 mutations are associated with palmar plantar psoriasis through activation usually of NF-Kappa B. CARD 14 is found on epidermal keratinocytes as well as dermal cells [13,14]. Antiinflammatory doses of folic acid reduce NF-kappaB [15].…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, Mossner et al have very recently observed the p.Asp176His mutation in two acral pustular psoriasis cases recruited in Estonia (Mossner et al, 2015). As the p.Asp176His substitution was not detected in any of the European datasets sequenced by the 1000 Genomes Project, it is not surprising that the variant did not appear in our APP cohort.…”
Section: Discussionmentioning
confidence: 56%